A SYSTEMIC FUNCTIONAL LINGUISTIC ANALYSIS OF THE TRANSITIVITY IN JOKOWI'S NEW VISION SPEECH - Suswanto Ismadi Megah (CAHAYA PENDIDIKAN, 2019)
This study deals with the investigation of the New Vision speech of President Joko Widodo (in Short, Jokowi). This study is aimed to identify what kinds of Jokowi tends to use one utterance comparared others. This study employed systemic functional linguistics theory of Halliday, particularly transitivity system as a tool of analysis, more specific this study process of transitivity. The data obtained from the victory speech of the presidential election, this speech was conducted during his inaugural speech occasion. The data was downloaded, then analyzed qualitatively. The study found that material process 31(36%), mental process 23(26%), relational process 27 (31%0, verbal there is no occurrence, behavioral there is no occurrence, and existential process 6(7%). This study concluded that Jokowi tended to uses material process, in contrast with verbal and behavioral processes which have no occurrences in his speech, it shows that he prefers to action to  show his action